Characterization and properties of recycled polypropylene (RPP)/chloroprene rubber (CR) blends - Nurul Azra, Bakaruddin (Universiti Malaysia Perlis (UniMAP), 2014)
The thermoplastic elastomer of recycled polypropylene (RPP) and chloroprene rubber (CR) blends were studied. Virgin polypropylene (PP)/chloroprene rubber blends were used as comparison. The blends were prepared by using Z-blade mixer at temperature 180°C and rotor speed of 50 rpm. The effect of blend ratios on tensile properties, swelling behaviour, morphology and thermal properties were investigated. It was found that increasing of CR content in PP/CR and RPP/CR blends increased the elongation at break and swelling percentage but decreased in tensile strength, Young’s modulus and crystallinity. The PP/CR blends indicated higher tensile and thermal properties than RPP/CR blends. The morphology study of PP/CR blends showed better interfacial interaction as compared to RPP/CR blends. The effect of dynamic vulcanization on the properties of RPP/CR blends indicated higher tensile strength, elongation at break, Young’s modulus and crystallinity but lower swelling percentage. The compatibilizers, maleic anhydride grafted polypropylene (MAPP) and maleic anhydride (MA) were used to enhance the tensile properties of blends. The addition of MAPP or MA has improved the tensile strength, Young’s modulus, elongation at break and crystallinity of blends. The micrograph SEM of tensile fracture surface of RPP/CR blends with dynamic vulcanized, MAPP or MA showed the interfacial interaction and adhesion between CR and RPP has been improved. The presence of MAPP or MA in RPP/CR blends exhibited better chemical resistance.